2013
DOI: 10.1182/blood-2012-10-457507
|View full text |Cite
|
Sign up to set email alerts
|

The C-type lectin receptor CLEC4M binds, internalizes, and clears von Willebrand factor and contributes to the variation in plasma von Willebrand factor levels

Abstract: Key Points• CLEC4M plays a role in the clearance of VWF.• CLEC4M polymorphisms contribute to the genetic variability of VWF plasma levels.Genetic variation in or near the C-type lectin domain family 4 member M (CLEC4M) has been associated with plasma levels of von Willebrand factor (VWF) in healthy individuals. CLEC4M is a lectin receptor with a polymorphic extracellular neck region possessing a variable number of tandem repeats (VNTR). A total of 491 participants (318 patients with type 1 von Willebrand disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
122
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(127 citation statements)
references
References 53 publications
5
122
0
Order By: Relevance
“…Recently, the C-type lectin receptor CLEC4M, the carbohydrate receptor Siglec-5 and scavenger receptor class A member 5 (SCARA5) have been shown to interact with VWF. [30][31][32] Interestingly, transfected HEK293 cells over-expressing CLEC4M or Siglec-5 were shown to efficiently internalize VWF. [30][31][32] The lack of VWF internalization observed in iDCs suggests that CLEC4M, Siglec-5 and SCARA5 are not involved in binding of VWF to dendritic cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the C-type lectin receptor CLEC4M, the carbohydrate receptor Siglec-5 and scavenger receptor class A member 5 (SCARA5) have been shown to interact with VWF. [30][31][32] Interestingly, transfected HEK293 cells over-expressing CLEC4M or Siglec-5 were shown to efficiently internalize VWF. [30][31][32] The lack of VWF internalization observed in iDCs suggests that CLEC4M, Siglec-5 and SCARA5 are not involved in binding of VWF to dendritic cells.…”
Section: Discussionmentioning
confidence: 99%
“…VWF specific peptides were identified using Proteome Discoverer and subsequently HLA-DRB1 genotype specific core peptides were predicted using NetMHCpan 2. 30 Our knowledge on the etiology and characteristics of this unwanted immune response remains limited. 36 Genetic studies have shown that allo-antibody development to VWF occurs in patients with deletions, frameshift and nonsense mutations.…”
Section: Discussionmentioning
confidence: 99%
“…105 Interestingly, a relationship between the number of tandem repeats in the CLEC4M gene and levels of VWF activity and antigen was observed when analyzing plasma samples from VWD patients. Apparently, sequence variations in VWF receptors may modulate the efficiency by which they remove VWF from circulation.…”
Section: Clec4mmentioning
confidence: 99%
“…The binding of a C-type lectin (CLEC4M), with VWF has previously been shown to enhance the internalisation of VWF by the host cells and alter plasma levels of VWF (Rydz et al 2013). In previous reports, proteins containing the VWF domain are localised in nematode intestine and suggested to play critical roles in cell adhesion and platelet aggregation (Wohner et al 2012).…”
Section: Blood Ligaedsmentioning
confidence: 99%